MODEL EFISIENSI PASAR: SEBUAH STUDI PENGARUH MUSIMAN DI BEI EMITEN LQ 45 TAHUN 2010-2012 - Syahril Djaddang; Indah Masri; Riska Yustisiana (Jurnal Keuangan dan Perbankan, 2014)
There is seasonal anomaly or calendar effect in financial markets called the Monday effect, week four effect and rogalsky effect. The presence of these anomalies violates the weak form of market efficiency because stock returns are not random, but are predictable based on certain calendar effects. The objective of this research is to empirically re-examine the seasonal anomaly. The sample used in this study are the Indonesian Stock Exchange Emiten LQ 45 Tahun 2010 – 2012. The major conclusion of this study is that seasional anomally like Monday effect, week four effect and rogalsky effect are not significantly for the sample Indonesian Stock Exchange Emiten LQ 45 Tahun 2010 – 2012. The results of this study indicate that the occurrence of anomalies in market efficiency IDX is evidence that seems inconsistent with the theory of the efficient market hypothesis (EMH) in which all the information in the stock market absorbed by market participants such as, Investor, the Issuer and the Guarantor influenced the effects of different trade for example, the effects of seasonal / calendar, resulting in the phenomenon of effect Thursday.